SMME readiness framework for smart manufacturing adoption using critical realism: Knowledge and construction phase - Lucas Gumbi; Hossana Twinomurinzi (Journal of Innovation & Knowledge)
Smart manufacturing (SM) has emerged as a viable solution for small, medium and micro enterprises (SMMEs) to remain sustainable and globally competitive. However, many SMMEs are not ready for SM and the existing frameworks for SM adoption are unsuitable for supporting SMMEs, as they do not address context-specific preconditions. The objective of this study was to empirically develop a suitable conceptual framework for supporting SMME readiness for SM adoption. A critical realism research cycle using the emergent theory development approach was chosen for the study. A qualitative research design, utilizing multiple case studies, was adopted. The study found that a suitable SMME readiness framework for SM adoption should consider SM Knowledge Competence (SMKC), SM Relative Advantage (SMRA), and SM Compatibility (SMC) as preconditions for SM adoption, as well as Self-Directed Digital Learning (SDDL), Business Model Innovation (BMI), Entrepreneurial Orientation (EO) and a Culture of Innovation (CoI) as factors influencing these preconditions. Furthermore, the study revealed that a CoI is an enduring structure with generative powers in the real domain; SDDL, BMI and EO are causal mechanisms prevailing in the real domain when the generative powers of CoI are triggered or activated; and SMKC, SMRA, and SMC are the actions (preconditions) that are triggered in the empirical domain when causal mechanisms are activated. The findings also highlighted stark social and cognitive differences between high-tech SMMEs and non-high-tech SMMEs.